Latent Health Status Trajectories in Individuals With New or Worsening Claudication Symptoms - Scott Grubman; Gaëlle Romain; Jacob Cleman; Lindsey Scierka; Carmen Pajarillo; Jonathan Kluger; Carlos Mena‐Hurtado; Kim G. Smolderen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background While peripheral artery disease care for claudication aims to improve health status (symptoms, physical function, and quality of life), health status trajectories remain unclear. We aimed to determine health status trajectories and explore baseline factors associated with treatment nonresponsiveness. Methods Data were derived from the PORTRAIT (Patient‐Centered Outcomes Related to Treatment Practices in Peripheral Arterial Disease: Investigating Trajectories) registry of patients with claudication symptoms presenting to vascular specialty clinics across the United States, Australia, and Netherlands. The Peripheral Artery Questionnaire was used to measure the health status at baseline and 3, 6, and 12 months. Latent trajectory modeling enabled the classification of patients into latent Peripheral Artery Questionnaire trajectory subgroups over 12 months. These subgroups were categorized as “responsive” or “nonresponsive,” depending on whether the 12‐month increase in mean Peripheral Artery Questionnaire score was greater than or equal to the clinically meaningful threshold of 10 or not, respectively. Sequential hierarchical multivariable logistic regression assessed baseline factors associated with a nonresponsive versus responsive trajectory. Results The cohort was composed of 1204 patients (62.5% men and aged 67.5±9.4 years). Five latent trajectory subgroups were identified: consistently high (33.3%), high maintained (8.1%), high transient (12.9%), moderate maintained (33.2%), and consistently low response (12.5%) with mean Peripheral Artery Questionnaire improvements of +16.8, +59.4, +7.6, +24.0, and +8.6, respectively. Nonresponsive clinical trajectory was associated with prior cerebrovascular accident, sleep apnea, alcohol use disorder, and worse depressive symptoms. Conclusions Individuals with claudication display heterogenous recovery trajectories. Roughly 25% experienced no health status response at 12 months after treatment, which was associated with medical and psychosocial factors. Further emphasis should be placed on a biopsychosocial model of peripheral artery disease care.